Teaching competencies for Teaching and Research from the perspective of professional sustainability (Research, Society and Development, 2021)
Demands of society impose challenges to the Higher Education teacher, facing the internationalization, cultural diversity, new educational conceptions and the demand for academic production. Faced with this reality, the idea arises that the teaching competences need to be sustainable, that is, flexible, adaptable and strategic. With this argument, it is questioned what dimensions define the competences of the Higher Education teacher in the context of their professional sustainability. In order to do so, the objective is to dimension teacher competences for teaching and research and to understand them in the light of current professional demands. The research presents a quantitative step, in which it carried out Exploratory Factor Analysis and Confirmatory Factor Analysis, based on the answers (213 teachers) to the (adapted) questionnaire of the Pereira instrument (2007); and qualitative, based on three semi-structured interviews (managers of the area of Teaching, Research and Extension), identifying dimensions in the quantitative phase to the contents, when, through co-occurrences, it was discussed about sustainable teacher competences. Sustainability is associated with the grouping of the six dimensions, which were: flexibility, which unfolds in empathy, proactivity and adaptation; to the ability with management, in the sense of know-how in front of the daily activities; to the didactic-pedagogical potential, which combines knowledge in harmony with an interactive and communicative environment; to ethical commitment, to social and political responsibility; to Innovation and Cooperation, in search of innovative formulations.